Insurance Construction Services In Infrastructure Development - Dimas Aulia Azizi (Yuridika, 2019)
The Construction Services Insurance Agreement has an important role in infrastructure development in Indonesia. It is considering that at present, the Indonesian government is very active in building infrastructure in various corners of the region in the framework of equitable economic stability. The guarantor, in this case, the insurance company provides guarantees in terms of planning up to maintenance. Or before construction up to post-development within a certain period. Insurance agreements made with a variety of considerations, including; protect national interests, avoid contractors who default or have bad intentions, geographical factors in an area, and so forth. But on the other hand, it also to protect the interests of contractors or construction service providers (the insured). For this research, the focus is on the accountability of construction service providers as consumers of insurance companies because construction service providers require insurance companies to transfer some of the risks while carrying out development projects. If in the course of the project an undesirable event occurs starting from the collapse of the building, damage to heavy equipment and so on, which fall within the scope of the object of the insurance agreement, the construction service provider can file a claim against the insurance company to compensate the loss suffered by the construction service provider. Thus it is necessary to analyze the legal relationships and procedures between construction service providers and insurance companies related to infrastructure development. In analyzing and answer the legal issues above, the research methods used are the statute approach (based on applicable laws). And the conceptual approach (based on legal concepts or theories from legal experts).